Assessment of IL-8 and TNF-α Status as Inflammatory Mediators in Celiac and Non-Celiac Gluten-Sensitive Disease - Hilal , Murtadha Alaa; Hameed, Wasan Sami (Iraqi Journal of Science, 2026)
Celiac disease (CeD) and non-celiac gluten sensitivity (NCGS) are disease conditions associated with exposure to a protein called gluten. That displays overlapping symptoms but distinct immune mechanisms. The study aimed to evaluate serum levels of Interleukin-8 (IL-8) and Tumour Necrosis Factor-alpha (TNF- α) in Iraqi patients with CeD and NCGS compared to healthy controls. This case-control study enrolled 80 patients diagnosed with coeliac disease, 20 gluten-sensitive patients, and 80 healthy individuals aged between 18-50 years; this study was conducted in Al-Najaf, Iraq, between August and December 2024. CeD patients exhibited significantly elevated IL-8 and TNF-α levels compared to NCGS and controls, with a consequent p < 0.001. Anti-tTG Ig was positive and correlated with IL-8(p=0.001) but moderately with TNF-α (p=0.012). For NCGS, moderate positive correlations were found between anti tissue-transglutaminase-IgA and IL-8 (p= 0.020) and tTG.IgG and IL-8 (p=0.037). The present study reveals that CeD exhibits chronic inflammation marked by IL-8 and TNF-α elevation. Furthermore, IL-8 can serve as a predictive biomarker for distinguishing between NCGS and CeD; however, additional study is needed for NCGS.